2022
DOI: 10.26803/ijlter.21.5.21
|View full text |Cite
|
Sign up to set email alerts
|

Life Satisfaction among Adolescents: Comparison of Adolescents Attending Music and Sports Programs and Those Who Do Not

Abstract: Life Satisfaction among Adolescents: Comparison of Adolescents Attending Music and Sports Programs and Those Who Do Not

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Another study which examined differences in life satisfaction between adolescents who participated in sports programs and those who did not, found that participants who participated in sports programs had higher life satisfaction rates than those who did not participate in such extracurricular activities. recommends promoting sports education among children and adolescents (Šimunović, & Olčar, 2022). Another study aiming to examine the link between physical activity and life satisfaction on adolescents revealed that there is a positive connection between physical activity and life satisfaction through the mediating role of perceptions of thinness and overweight, and emphasizes that it mediates the effect of physical activity on life satisfaction (Meyer et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Another study which examined differences in life satisfaction between adolescents who participated in sports programs and those who did not, found that participants who participated in sports programs had higher life satisfaction rates than those who did not participate in such extracurricular activities. recommends promoting sports education among children and adolescents (Šimunović, & Olčar, 2022). Another study aiming to examine the link between physical activity and life satisfaction on adolescents revealed that there is a positive connection between physical activity and life satisfaction through the mediating role of perceptions of thinness and overweight, and emphasizes that it mediates the effect of physical activity on life satisfaction (Meyer et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, life satisfaction is directly related to family satisfaction (Valdemoros San Emeterio et al, 2020) and represents one of its specific areas (Perugache Rodríguez et al, 2016). In this sense it is important to foster programs that promote better levels of self-esteem and family satisfaction to improve the levels of life satisfaction as observed in different studies (Caballero-García and Sánchez Ruiz, 2021;Lee and Tsai, 2022;Šimunović and Olčar, 2022).…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%